Ideologi: Faktor Konflik dan Kegagalan Timur Tengah - Muttaqin, Muhammad Zainal (Nation State: Journal of International Studies, 2018)
The following article explains how Western ideologies become major factor of conflicts and failures in the Middle East. In this paper the author looks from the perspective of ideological hegemony. Ideology undermines the political and economic systems that cause social inequality and accelerate the outbreak of conflict in the Middle East. The author raised Syria and Libya as examples to prove the factors that led to the conflict. The author argues that the main cause of the Middle East conflict is the influence of Western ideology that cannot be accepted by government in power or even the people, so that it triggers conflicts and even war. Democracy which is an accepted model in various countries cannot be applied in the Middle East. The author also criticized the failure of democracy implementation and liberal economies in the Middle East.